2011
DOI: 10.5134/159487
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Characteristics of DMSP Lyase Activity in Seawater and Phytoplankton Cultures

Abstract: Dimethylsulfoniopropionate (DMSP) is produced by a wide variety of marine phytoplankton, and it can be enzymatically cleaved to dimethylsulfide (DMS) and acrylate by DMSP lyases. DMS formation in the sea plays an important role in the global sulfur cycle, yet the factors regulating production of DMS are poorly understood. We evaluated various procedures used for in vitro assays of DMSP lyase activity (DLA) of cells captured on filters. We also compared in vitro DLA from plankton material collected from diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Thus, > 98% of the DMSP lyase activity was associated with the phytoplankton cells. This finding is consistent with previous studies that have shown that the majority of DMSP lyase activity is associated with phytoplankton size classes in seawater and phytoplankton cultures (Steinke et al 2002, Yost & Mitchelmore 2009, Harada & Kiene 2012. While some bacteria may have been attached to the Phaeocystis cells, our preliminary studies on the de novo peptide sequencing of the partially purified Phaeocystis DMSP lyases indicated lack of homology with the 6 known proteins of bacterial DMSP lyases (B. R. Mohapatra et al unpubl.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, > 98% of the DMSP lyase activity was associated with the phytoplankton cells. This finding is consistent with previous studies that have shown that the majority of DMSP lyase activity is associated with phytoplankton size classes in seawater and phytoplankton cultures (Steinke et al 2002, Yost & Mitchelmore 2009, Harada & Kiene 2012. While some bacteria may have been attached to the Phaeocystis cells, our preliminary studies on the de novo peptide sequencing of the partially purified Phaeocystis DMSP lyases indicated lack of homology with the 6 known proteins of bacterial DMSP lyases (B. R. Mohapatra et al unpubl.…”
Section: Resultssupporting
confidence: 92%
“…The extraction of DMSP lyase was performed as reported previously with some modifications (Harada & Kiene 2012). Briefly, algal pellets from each flask were resuspended in 5 ml of ice-cold 200 mM TrisHCl buffer (pH 7.5) containing 500 mM NaCl, 2 mM dithiothreitol (DTT) and 0.1% (v/v) Triton X-100, followed by vigorous vortex mixing and centrifugation at 3500 × g (4°C) for 15 min.…”
Section: Dmsp Lyase Extractionmentioning
confidence: 99%
“…In addition, these molecules take part of an intracellular antioxidant cascade as ROS scavengers (Sunda et al, 2002). Phytoplankton cells may probably use DMSP and derivatives for different functions, they are not necessarily exclusive (Harada and Kiene, 2011). Indeed, multifunctional osmolytes like DMSP are more likely to be selected by phytoplankton species (Welsh, 2000).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…4). In the late exponential phase of P. globosa and H. triquetra which possess DLA, DMSPp of senescent cells was quickly cleaved into DMS and then oxidized into DMSO whereas only DMSP can be oxidized into DMSO in DMSP-producing diatoms which do not possess DLA (Harada and Kiene, 2011). DMSP-lyase may be used to regulate DMSP concentration either for the greater efficiency of its by-products (DMS and acrylate) as antioxidants (Sunda et al, 2002) and grazing deterrents, or as a disposal of the over-accumulated DMSP for osmotic regulation and overflow mechanism (Stefels and van Leeuwe, 1998).…”
Section: Dms(po)p Cell Quotas At Different Growth Stagesmentioning
confidence: 99%
“…DMSP is also a source of carbon (C) and S for heterotrophic organisms (Kiene and Linn, 2000a) and acts as a chemical cue for higher trophic level organisms (Steinke et al, 2002). These physiological functions are not necessarily exclusive (Harada and Kiene, 2011) and phytoplankton cells may use several of them.…”
Section: Introductionmentioning
confidence: 99%